Relationship between Manager's Self-Regulation and Leadership Performance in Kenya - Mwania, Jonathan (International Journal of Psychology, 2023)
Purpose: This study focused on the relationship between manager's self-regulation and leadership performance in South Eastern Kenya University, Kenya.It was conducted in South Eastern Kenya University. Methodology: The researcher employed purposive and census sampling technique in selecting a sample of 71 respondents. The target population included all the 75 managers in South Eastern Kenya University. Data was collected through administration of structured questionnaires with the selected respondents. The questionnaire used a five-point range Likert scale to assess strategic managers' self-regulation and leadership performance. The collected data was then processed and analyzed using both descriptive and inferential statistics with the aid of Statistical Package of Social Science (SPSS) version 28.0 for windows. The data was presented using tables. Findings: The findings of the study showed that there was a strong positive (r = 0.616, p=0.001) relationship between Self-regulation and leadership performance. Unique Contribution to Theory, Practice and Policy: The contribution to knowledge of this paper is that it provides a theoretical and practical contribution on the importance of helping strategic managers at the South Eastern Kenya University to attain higher levels of self-regulation. This is because self-regulation is known to have a strong influence on leadership performance. Basically, the study contributed to a theoretical enhancement of the current level of knowledge on the existing literature on self-regulation, achieved by testing empirically the managers' behaviour. In terms of the research practical contribution, the findings of the study could aid in the development of applied strategies at the work place. The findings of this study could help universities to boost the level of manager's self-regulation and this in turn may lead to the improvement in leadership performance. The study recommends that: the University administration should continually train their staff on the relationship between the managers' self-regulation and leadership Performance; they should employ personnel with high degree of self-regulation skills through conducting interviews with questionnaires that assess these attributes and invest heavily in teamwork activities so that they may have employees who have high degree of self-regulation.